The Politics of Electional Law in Indonesia - Moh Indra Bangsawan; Kukuh Ari Febrianto (Universitas Muhammadiyah Surakarta, 2023)
Less than a year from now the 2024 elections will be held. The preparatory stage is underway. That is, the election process has been running in such a way. The request to change the open proportional system seemed to be a stumbling block in the process of organizing the 2024 elections. Problems arose when a request registered with Case Number 114/PUU‐XX/2022 which essentially requested Indonesia to switch to a closed proportional election system was filed with the Constitutional Court. The request was submitted by the PDIP, represented by Demas Brian Wicaksono and five other individuals. This request gave birth to a polemic in the community. The cause of changes to the main foundation in holding elections, namely the electoral system, will greatly affect the whole series of democratic parties. Departing from these problems, the authors conducted a series of critical analysis studies to examine these issues.